Convergence and divergence of perfomances across the athletic events for men and women: A cross-sectional study 1960-2012 - Heazlewood, I.; Walsh, J. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
There is a perception that performances in athletic events, such as the sprints, throws distance and hurdles events are converging for the top athletes in each event where access to quality training methods and performances at international competitions are readily available for international ranked athletes. Some researchers cite biological reasons that may explain the suggested convergent tends in athletics. The research hypothesis and aim was to evaluate if performance convergence was occurring using the method of regression analysis of the mean of standard deviations, an index of performance dispersion or divergence, for the top 20 male and female athletes across the majority of athletic events from years 1960 to 2012. The results indicated that most male events have reached stasis, neither converging nor diverging whereas female events are currently undergoing performance convergence. Factors such as access to high performance coaches, sports scientist, relevant sports nutritionists and quality medical support are producing the level playing field that is now so level that minimal performance diversity exists between the top 20 male athletes across many events. The reverse situation applies to female athletes who are still displaying performance convergence and who are progressing towards a level playing field.